Microbiological, quality assessment of purified drinking water available to consumers at U.P. Visayas, Miagao, Iloilo. - Boltron, Patrice Irah Barandino (2015.)
The study involved the quality assessment of the purified drinking water from three refilling stations available for consumption in UPV, Miagao, Iloilo which were referred to as A, B, and C. The study also involved the assessment of the purified drinking water from the dining halls namely a, b, and c, that are supplied by the refilling stations A, B, and C, respectively. The purified drinking water from both the refilling stations and dining halls were subjected to microbiological assessment and physico-chemical tests. The microbiological assessment included the determination of Total Plate Count (TPC) and the Most Probable Number (MPN) of Coliforms while the physico-chemical tests included the determination of pH and the Total Dissolved Solids (TDS). The mean total plate counts for purified drinking water from refillig stations A, B, and C were 2.0x 104 CFU/ml, 7.4x103 CFU/ml, and 75 CFU/ml, respectively, with refilling station C having the lowest microbial count. For dining hall a, b, and c, the mean total plate counts were 4.0x105 CFU/ml, 2.0x105 CFU/ml, and 1.4x105 CFU/ml, respectively, with dining hall c having the lowest microbial count. For the MPN of coliforms, refilling station A, B, and c had 2.0x102 MPN/ml, 3.0x102 MPN/ml and 2.0x102 MPN/ml respectively. Total Plate Count and Most Probable Number of coliforms of both the refilling stations and the dining halls were accepted based on the standard value set by Department of Health (2007), thus safe for consumption. The pH of the purified drinking water from the three refilling stations ranged from 7.22-7.29 and the pH of the purified drinking water from the three dining halls ranged from 7.13-7.22 pH and TDS of purified drinking water from both refilling stations and dining halls were still under the acceptable value set by the Philippines National Standards for Drinking Water (2007) and DOH (2007).
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Water; Water treatment